"Her" Photographer: The Roanoke Live-Shot Murders and Visual Communication's Place in the Newsroom. Issue 3 (3rd July 2017) - Bock, Mary Angela; Lough, Kyser; Fadnis, Deepa
Abstract : This study analyzed coverage of the shootings of two journalists in Virginia in 2015. Coverage of journalism by journalists, or metajournalistic discourse, makes it possible to examine the way an interpretive community represents and reproduces professional norms. Working with the framework of Pierre Bourdieu's field theory, the analysis considers the way journalistic specialists maintain their identity, professional boundaries, and hierarchal relationships. This analysis focuses on how visual journalism, in particular, is presented to the news audience. Based on our findings, we argue that coverage of the Roanoke live-shot murders provides insight into the way journalism maintains its authority by highlighting affect and diminishing its constructed dimension.